Ebola Infection and Diabetes Mellitus - Sora Yasri; Viroj Wiwanitkit (Iranian Society of Pathology, 2016)
Diabetes mellitus is the common endocrine problem that affects millions of world population. The disease can be seen in every country around the world. It is recorded as one of the most common noninfectious disease at present. In the era of the new emerging diseases, the concern on the effect of new diseases on diabetes should be discussed. For example, in the case of new emerging zoonotic influenza infections, the effect of the new diseases on the clinical course of diabetes mellitus is mentioned (1). In addition, the interesting observation of the prevalence and severity of new emerging infections in the cases that has diabetes mellitus, as a concomitant disorder is also available in the literatures.